Genus Eremochares Gribodo (Hymenoptera: Sphecidae) in China with description of a new species - Yan, Cheng-jin; Ma, Li (Entomologica Fennica, 2015)
The species of the genus Eremochares Gribodo (Hymenoptera: Sphecidae: Ammophilinae) in China are revised. A new species, E. clypevariatus Yan&Ma, sp. n., is described and illustrated. The key to the Eremochares species of the world is updated to include the new species.